Los saberes de los exiliados republicanos viajan de España a Argentina - Alfredo F. Dantiacq-Sánchez (Les Cahiers ALHIM)
Relations between Spaniards and Argentines have been good since the beginning of this shared history. There are hundreds of examples and there is the particular situation that originates in the years of the Civil War that shakes the former mother country and, in the immediate aftermath, when intellectuals, politicians and journalists, doctors and lawyers, persecuted or threatened by the system that put an end to the Second Republic, to which they had adhered, makes their private and public life difficult. From this immense group, we selected a few, privileging those who worked in our environment, who, through the university chairs to which they accessed, professed a marked influence on young people and adults, since they allowed a ferment of renovating proposals. By offering to participate in teaching, one of the most delicate aspects of the exile was covered : job placement. For their part, they helped expand the contents of the programs, the approaches, the bibliography and stimulate a comparative criterion.